Tailoring drug and gene codelivery nanosystems for glioblastoma treatment - Silva, Jessica (2020)
Glioblastoma is the most common primary and aggressive brain tumour, with an increasing incidence worldwide. The prognosis of this disease is still poor, with a median survival time not exceeding two years. Standard-of-care therapy includes surgical resection, radio- and chemotherapy, but nearly all patients experience progression of the disease. This may be ascribed to the heterogeneity, invasiveness and resistance of tumour cells, along with the struggle that many chemical drugs present in effectively crossing the dual blood brain-blood brain tumour barrier. Considering the hurdles associated to traditional therapeutic approaches, there is a pressing need to improve patient care, as treatments currently available have little effect on the overall survival. Therefore, the use of adjuvant chemotherapeutics in combination with temozolomide, a first-line drug, and novel molecularly-targeted approaches against both tumor and stem cells and respective microenvironment are under investigation. This chapter addresses the development of innovative multi-target nanomedicines, comprising complementary chemo- (e.g. temozolomide) and gene therapeutic (antimiR and miRNA mimic) agents, combined with targeting ligands within a single nanostructure directed at the treatment of glioblastoma multiforme. The approach aims at providing significantly improved therapeutics, as treatments currently available have little effect on overall survival.